2009
DOI: 10.1016/j.neures.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine treatment causes delayed decrease in novelty-induced locomotor activity in mice

Abstract: Methamphetamine (METH) is a psychostimulant that causes damage to dopamine (DA) axons and to non-monoaminergic neurons in the brain. The aim of the present study was to investigate shortand long-term effects of neurotoxic METH treatment on novelty-induced locomotor activity in mice. Male BALB/c mice, 12-14 weeks old, were injected with saline or METH (i.p., 7.5 mg/kg × 4 times, every 2 hours). Behavior and neurotoxic effects were assessed at 10 days, 3 and 5 months following drug treatment. METH administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…These data indicate a dosagedependent reduction in apoptosis due to a reduction in oxidative stress by the protective application of amphetamine [15,19]. In accordance, Krasnova et al [16] observed that a high dosage of methamphetamine (Table 1) resulted in DNA fragmentation and cell death in the mouse striatum and cortex.…”
Section: Brain Injury and Amphetaminessupporting
confidence: 62%
See 1 more Smart Citation
“…These data indicate a dosagedependent reduction in apoptosis due to a reduction in oxidative stress by the protective application of amphetamine [15,19]. In accordance, Krasnova et al [16] observed that a high dosage of methamphetamine (Table 1) resulted in DNA fragmentation and cell death in the mouse striatum and cortex.…”
Section: Brain Injury and Amphetaminessupporting
confidence: 62%
“…Eight out of 13 preclinical trials in animals demonstrated beneficial effects of coupling of d-amphetamine administration with physical and cognitive training [17,19,[21][22][23][24][25][26] in improvement of motor and cognitive recovery after brain injury, whereas four studies [16,18,20,27] could not detect an improved recovery. Papadopoulos et al [17] even reported a full recovery to baseline performances, but only with the coupled therapy of amphetamine and physical training.…”
Section: Brain Injury and Amphetaminesmentioning
confidence: 99%
“…Several studies show that METH is toxic to neural cells, 4,[37][38][39] inclusively to progenitor cell cultures from embryonic rat hippocampus. 24 It is noteworthy that few studies have addressed the effect of METH on neurogenesis, 23,40,41 and indeed, little is known about the effect of METH on stem/progenitor cells toxicity and capacity of neuronal differentiation, especially in the SVZ.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also documented METH-induced effects on motor or cognitive performance in both animal models and humans who abuse METH (Friedman et al, 1998; Chang et al, 2005; Salo et al, 2009; Krasnova et al, 2009; Achat-Mendes et al, 2005; Izquierdo et al, 2010; Daberkow et al, 2007, 2008; Boger et al, 2009; Hall et al, 2008). In rodents, for example, acute METH increases open-field locomotor activity that has been shown to accompany altered DA neurotransmission (Hall et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term effect, however, includes psychomotor deficits such as decreased locomotor activity. These deficits persist even when striatal DA recovers (Boger et al, 2009; Krasnova et al, 2009). Friedman et al (1998) demonstrated depleted DA levels in the striatum 65 days after METH, which is attenuated when measured at 265 days.…”
Section: Introductionmentioning
confidence: 99%